2022
DOI: 10.1155/2022/7207846
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Possibility of Middle Ear Discharge for COVID-19 Test Material

Abstract: The COVID-19 pandemic is still ongoing, and new variants continue to emerge. Various examination methods and sampling specimens are continuously being developed and published. The standard for sampling is in the nasopharynx. However, in children, this is often uncomfortable and at risk of eliciting complications. Therefore, it is necessary to look for other alternative sampling sites such as fluid from the middle ear. Scientific evidence shows that the middle ear can be a place for the attachment and growth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…However, only two cases with otitis media with effusion have shown the presence of the SARS-CoV-2 isolated from the middle ear, while other cases were tested positive for SARS-CoV-2 nucleic acid in the nasopharynx without certain evidence of SARS-CoV-2 infection in the middle ear [16] [17] [18] [19] [20]. Here, we report a group of outpatient cases in which the nucleic acid of SARS-CoV-2 was tested positively in the middle ear effusion, demonstrating the previous speculation that the SARS-CoV-2 can infect the middle ear [12] [21] [22] [23].…”
Section: Introductionsupporting
confidence: 57%
“…However, only two cases with otitis media with effusion have shown the presence of the SARS-CoV-2 isolated from the middle ear, while other cases were tested positive for SARS-CoV-2 nucleic acid in the nasopharynx without certain evidence of SARS-CoV-2 infection in the middle ear [16] [17] [18] [19] [20]. Here, we report a group of outpatient cases in which the nucleic acid of SARS-CoV-2 was tested positively in the middle ear effusion, demonstrating the previous speculation that the SARS-CoV-2 can infect the middle ear [12] [21] [22] [23].…”
Section: Introductionsupporting
confidence: 57%
“…Kadriyan proposes middle ear fluid as an alternative diagnosis for COVID-19. 8 Furthermore, Frazier et al 9 identified SARS-CoV-2 in the middle ear and mastoid of deceased individuals with COVID-19, although the duration of virus presence in MEE was not reported. Nevertheless, both studies suggest the potential existence of SARS-CoV-2 within the middle ear, potentially playing a role in the emergence of middle ear disorders subsequent to COVID-19.…”
Section: Introductionmentioning
confidence: 99%